2015
DOI: 10.1177/0300060514562056
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in methods of and reasons for suicide in Turkey between 1990 and 2010

Abstract: Objective: To analyse suicides occurring in Turkey between 1990 and 2010 according to sex, age, reason and method. Methods: Data concerning suicides occurring in Turkey between 1990 and 2010 were obtained from annual records published by the Turkish Statistical Institute. Data were analysed according to sex, age, reason for suicide and suicide method. Results: The crude suicide rate was 2.42 per 100 000 population in 1990 and 4.02 per 100 000 population in 2010. The highest number of suicides was seen in those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…One of the studies conducted in Switzerland indicated that Turkish women under the age of 25 accounted for the 38.6% of all attempted suicides [ 41 , 42 ]. Similar findings regarding the high frequency of young women among people who attempted [ 43 , 45 , 46 , 48 , 52 , 55 ] or died by suicide [ 12 , 28 , 62 , 63 ] were reported in traditional areas in Turkey. For instance, an article with suicide data derived from the annual reports of Turkey’s suicide statistics (between 1998 and 2000) indicated a high number of suicides among girls under 15 [ 62 ].…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…One of the studies conducted in Switzerland indicated that Turkish women under the age of 25 accounted for the 38.6% of all attempted suicides [ 41 , 42 ]. Similar findings regarding the high frequency of young women among people who attempted [ 43 , 45 , 46 , 48 , 52 , 55 ] or died by suicide [ 12 , 28 , 62 , 63 ] were reported in traditional areas in Turkey. For instance, an article with suicide data derived from the annual reports of Turkey’s suicide statistics (between 1998 and 2000) indicated a high number of suicides among girls under 15 [ 62 ].…”
Section: Resultssupporting
confidence: 77%
“…The epidemiology of suicidal behaviour of Turkish women (residing in Turkey) shows that the suicide rate among Turkish women aged 15–24 in Eastern Turkey is twice as high as their male counterparts since 2000 [ 9 ]. These finding were recently replicated by an annual report on suicide statistics drawn from Turkey’s general population [ 12 ]. Similarly, hospital registration data in Southeast Turkey has shown that attempted suicide rates were 4.15 times higher among young women 15–24 years old who presented at emergency departments compared to men of the same age as well as older men and women [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…They usually have a variety of pressure coming from job, marriage, and social interactions. If they cannot cope with setbacks and changes, suicide was possibly selected to escape from the frustration [ 13 , 14 ]. World-wide, men die from suicides 2–3 times more often than women, but women make more suicide attempts, which is called the “gender paradox” in suicide [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The selected methods for suicide differ in Turkey according to gender. Methods including violent action such as using a firearm, a sharp instrument or jumping off a high place are methods which dis-play male characteristics while women prefer methods such as consuming chemical substances (Aktaş, 2014;Öner et. al., 2015).…”
Section: Suicides In Turkey According To the Methods Usedmentioning
confidence: 99%